A bond‐based peridynamic model considering effects of particle rotation and shear influence coefficient. (17th October 2019) - Zheng, Guojun; Shen, Guozhe; Xia, Yang; Hu, Ping
Summary: The classical bond‐based peridynamic (BPD) model is limited with a fixed Poisson's ratio. To overcome this limitation, an improved BPD model is proposed to analyze the deformation and crack propagation of microelastic brittle materials with emphasis on varying Poisson's ratios. In the proposed model, the bond is subjected to axial and transverse pairwise forces, and the particle rotation angle is added to eliminate the additional bending moment caused by transverse forces, which is a key factor to satisfy the balance of angular momentum exactly. As a result, the bond not only has axial displacement but also has transverse displacement and particle rotation. This extension in the displacement mode overcomes the limitation of the fixed Poisson's ratio in the classical BPD model. The simulation results demonstrate the precision of the improved BPD model and prove its ability to predict deformations and crack propagations.